2013
DOI: 10.1371/journal.pone.0076523
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Novel CSF Tau and ptau Biomarkers for Alzheimer’s Disease

Abstract: Cerebral spinal fluid (CSF) Aβ42, tau and p181tau are widely accepted biomarkers of Alzheimer’s disease (AD). Numerous studies show that CSF tau and p181tau levels are elevated in mild-to-moderate AD compared to age-matched controls. In addition, these increases might predict preclinical AD in cognitively normal elderly. Despite their importance as biomarkers, the molecular nature of CSF tau and ptau is not known. In the current study, reverse-phase high performance liquid chromatography was used to enrich and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
169
4
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(190 citation statements)
references
References 57 publications
13
169
4
4
Order By: Relevance
“…Because in our study the Tau protein was trypsin digested before analysis, we did not have a direct access to the exact fragments present in CSF. However, our results are coherent with the study of Meredith et al [30] which described N-and C-terminal fragments associated with a 17 kDa central core fragment. Differences in output observed between the present study and those by Portelius et al [28] and McAvoy et al [27] can be accounted for in various ways different origins.…”
Section: Discussionsupporting
confidence: 93%
“…Because in our study the Tau protein was trypsin digested before analysis, we did not have a direct access to the exact fragments present in CSF. However, our results are coherent with the study of Meredith et al [30] which described N-and C-terminal fragments associated with a 17 kDa central core fragment. Differences in output observed between the present study and those by Portelius et al [28] and McAvoy et al [27] can be accounted for in various ways different origins.…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with previously published studies (35)(36)(37). Recently, improved characterization of CSF Tau using reverse-phase high performance liquid chromatography led to the evaluation of five total Tau assays side by side, and the two assays containing N-terminal sequences exhibited the most significant differences between AD and control CSF (66). This suggests that the use of mAbs such as ADx215, recognizing the N terminus of Tau, may indeed improve diagnostic accuracy.…”
supporting
confidence: 90%
“…Importantly, despite the observation that primary tauopathies present severe neurodegeneration and tau pathology, CSF T-tau and Ptau show no clear change (Masters et al 2015).This may be due to the fact that current tau immunoassays are based on antibodies binding to the mid region of tau and may miss pathogenic tau due to truncation or masking during oligomer/aggregate formation. Recent studies suggest that CSF tau consists of several protein fragments (Meredith et al 2013, Barthelemy et al 2016, and metabolic processing of tau into N-, mid and C-terminal fragments may also be key for secretion, aggregation and spreading pathology of tau, and may differ between the tauopathies (see below). Furthermore, the potential of tau oligomers or cis-tau variants (Kondo et al 2015) as specific biomarkers for tauopathies has not been explored.…”
Section: Cerebrospinal Fluid (Csf) Sampling With Emphasis On Tau Fragmentioning
confidence: 99%
“…Recent data have shown that fragments of tau are able to cross the blood-brain barrier with different rates, depending on the precise amino acid sequence (Banks et al 2016). The CSF tau profile is composed entirely of tau fragments rather than full-length protein, with different fragmentation patterns dependent on disease state and progression (Johnson et al 1997;Meredith et al 2013). CSF tau CTF and NTF levels are decreased in PSP, while increases were observed in AD (Wagshal et al 2015).…”
Section: Cerebrospinal Fluid (Csf) Sampling With Emphasis On Tau Fragmentioning
confidence: 99%